IMPLEMENTASI RESCHEDULING, RESTRUCTURING, DAN RECONDITIONING SEBAGAI UPAYA PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH DI BMT BEE MASS NGAWI - Maslukhin Ansori; hamdani hamdani (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Syari ah banking has become a common reality in Indonesia, including in theProvince of East Java, especially in the city of Ngawi. The business activities of Islamic financial institutions include collecting funds from the public in the form of savings and channeling them to the public in order to improve the standard of living of the common people based on sharia principles. Baitul Maal Wa Tamwil (BMT) Bee Mass Ngawi applies Murabahah and Al-Ijarah financing products, which are applied to microfinance for customers, with the aim that customers can utilize or own this business equipment to support their business activities. This research uses qualitative research, which produces descriptive and written data through information from the people involved in the object, in order to get a systematic picture of the factors and practices of implementing rescheduling, restructuring, and reconditioning as an effort to settle the problematic murabaha financing at the Baitul Maal Wa Tamwil (BMT) Bee Mass Ngawi. Based on the results of field research to answer questions about the implementation of rescheduling, restructuring, and reconditioning as an effort to solve problematic murabahah financing at Baitul Maal Wa Tamwil (BMT) Bee Mass Ngawi, it can be concluded that problematic financing is caused by internal and external factors, and the main factors in this factor are managerial factors. Settlement of rescue in financing restructuring is an effort made by Baitul Maal Wa Tamwil or other financial institutions to help customers settle their obligations based on sharia principles, saving problematic financing by rescheduling, rearranging, reconditioning, and changing the procedural policies of financial institutions.